TINJAUAN YURIDIS TERHADAP PUTUSAN NOMOR 131/Pdt.G/2023/PN Sgr TERKAIT PERKARA PERCERAIAN BERDASARKAN UNDANG-UNDANG NO 16 TAHUN 2019 TENTANG PERKAWINAN - Dani Ilham; Ni Ketut Sari Adnyani; Muhamad Jodi Setianto (Universitas Pendidikan Ganesha, 2023)
This research aims to (1) find out and analyze DECISION NUMBER 131/Pdt.G/2023/PN Sgr Regarding Divorce Cases in Buleleng Regency; and (2) Review and analyze the Judge's Considerations in Divorce Cases in Decision Number 131/Pdt.G/2023/PN Sgr. In this research, the type of research used is empirical legal research using descriptive research characteristics. The data and data sources used are primary data and secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data collection techniques used are document study techniques, observation techniques and interview techniques. The sampling technique used was non-probability sampling technique and the subject determination used purposive sampling technique. Next, the data obtained is processed and analyzed qualitatively. The research results show that (1) Marriage breakdown is caused by divorce, where divorce can occur due to several factors, especially infidelity. (2) The judge's consideration in giving a divorce decision considering that the defendant was proven to have had an extramarital affair and violence against the plaintiff which caused disharmony in the household, the judge granted the plaintiff's lawsuit.